Dietary Guidelines for Americans: Implications for Primary Care Providers. (January 2016) - Mosher, Amber L.; Piercy, Katrina L.; Webber, Bryant J.; Goodwin, Stephanie K.; Casavale, Kellie O.; Olson, Richard D.
In the United States, high rates of obesity and chronic disease impose serious consequences on the population's health and health care system. Primary care providers are critical to broad prevention efforts aiming to reduce the burden of chronic disease in the nation and play an important role in addressing lifestyle behaviors that can result in illness and premature death. Unhealthy dietary behaviors largely contribute to morbidity and mortality in the United States despite national efforts to improve the nutritional quality of the typical American diet. This article discusses a comprehensive set of national evidence-based recommendations known as the Dietary Guidelines for Americans that can support primary care providers' efforts to improve patient outcomes through optimal nutrition and healthy lifestyle behaviors. This article also describes basic behavioral counseling techniques primary care providers can incorporate into time-limited patient encounters to help improve the dietary and physical activity behaviors of their patients.